Germination behavior of Gynura crepidioides Benth., Portulaca oleracea L., and Dactyloctinium aegyptium (L.) Aschess and Schwein - Gacutan, Maria Vicenta Cuevas 1942-
The germination behavior of seeds of Gynura crepidioides Benth., Portulaca oleracea L. and Dactyloctinium aegyptium (L.) Aschess and Schwein was studied. It was observed that seeds of Gynura are light-requiring and newly-harvested seeds respond most favorably to 5 cycles in a 6-hour photoperiod. Continuous light was found to be inhibitory to germination. Gibberellic acid at concentrations of 50 and 100 mg/liter was able to substitute for the light requirement but in all concentrations used sensitivity to light was greatly enhanced. At a concentration of 100 mg/liter the critical period was lowered to 5 min. and if given a 6-hour photoperiod the number of inductive cycle is reduced from 5 to 1. Gynura seeds stored for 3 months or more were found to have lost their photoperiodic requirement and seeds germinated equally in short or continuous irradiations. Seeds of Portulaca appeared to be dormant upon harvest. Germination was gradually attained by dry storage at room temperature. Dormancy of newly-harvested seeds was most favorably overcome by incubating (imbibing the seeds at 44 degrees C) in the dark for 5 days followed by a 24-hour exposure to light. This light requirement is present only in dormant, incubated seeds but not in after-ripened seeds. Gibberellic acid was not able to release the seeds from their dormant state. It however, promoted germination of dormant incubated seeds in the light. Dactyloctenium also proved to be dormant upon harvesting and, like Portulaca, an after-ripening process was required. Dormancy was brought about by the presence of a germination inhibitor which could be leached by diethyl ether, ethyl alcohol or water, in the decreasing order of effectiveness. A promotion of germination in light over the dark was observed in leached seeds and also those undergoing the after-ripening process. Promotion, however, decreases with the extent of after-ripening and with the efficiency of leaching solvent. Light seems to bring about an inactivation or destruction of some germination inhibitors in Dactyloctenium seeds.